APPALACHIAN BLACK FIDDLING: HISTORY AND CREATIVITY - DjeDje, Jacqueline Cogdell (International Library of African Music, 2020)
Discussions on Appalachian music in the United States most often evoke images of instruments such as the fiddle and banjo, and a musical heritage identified primarily with Europe and European Americans, as originators or creators, when in reality, many Europeans were influenced or taught by African-American fiddlers. Not only is Appalachian fiddling a confluence of features that are both African- and European-derived, but black fiddlers have created a distinct performance style using musical aesthetics identified with African and African-American culture. In addition to a history of black fiddling and African Americans in Appalachia, this article includes a discussion of the musicking of select Appalachian black fiddlers.
Keywords: Old-time music; European Americans; African Americans; Country music; Musical instruments; Appalachian region; United States; Appalachia; Fiddle (Instrument); Black Fiddling; Hillbilly Music; African Music